State Universityâs Institusional Repository as a Storage for Civitas Academia Intelectul Property - Srirahayu, Dyah Puspitasari (Universitas Airlangga, 2015)
Many works - works the academic community that has not been published so that the intellectual property Â of Â an Â educational Â institution Â is Â not Â widely Â known Â by Â the Â general Â public. Â Institutional repository Â created Â and Â used Â to Â manage Â the Â results Â of Â these Â works Â that Â can Â be Â accessed Â by Â all people. Â This Â study Â aimed Â to Â describe Â the Â institutional Â repository Â of Â high Â perguruang Â country Â in Java Â Timursebagai Â container Â to Â the Â intellectual Â academic Â community Â views Â of Â content, Â the software Â used Â unit Â that Â houses, Â and Â ratings Â on Â Webometrik. Â This Â study Â uses Â a Â quantitative approach Â with Â descriptive Â methods. Â The Â population Â used Â in Â this Â study Â are Â all Â the Â institutional repository of public universities in East Java, which already are online. The sampling technique is the total sampling. The results of this study found that 50% of state universities in East Java has an Â IR that can be accessed via the internet, 100% of existing Â IR content is scientific output, the software used various existing GDL, DSpace, Eprints and others, and IR state universities in Java East 66.7% was ranked in webometrik.